Israel/Palestine : Parameters for a Two-State Settlement (International Crisis Group Avenue Louise 149, 1050 Brussels, Belgium, 2016)
The collapse of U.S.-led Israeli-Palestinian talks in 2014 led to political instability, rising violence and settlement expansion. To improve his successors peace-making chances, President Obama should push for a new UN Security Council resolution setting out the basic parameters of a deal.
Keywords: Guerra; Paz; Israel; Palestina